Terapia de fotobiomodulação em doença hepática gordurosa não alcoólica–estudo piloto - Oliveira, Luz Marina Gonçalves de Araujo (2019)
In today's world, the lifestyle changes for the past 5 decades, has provided junk food‘s advantage by anytime, anywhere. In this unregulated food process, one finds a large amount of sugar and un saturated fats in the blood, conducting to obesity, which has become a global outbreak, leading to hepatic steatosis in a frightening and monumental scale. OBJECTIVE: This study aimed to evaluate the therapeutic effect and safety of photobiomodulation ther apy ( by sublingual transvascular ILIB Intravascular L ight Irradiation of Blood technique in patients with non alcoholic fatty liver disease ( evaluated by ultrasonography. The effects of PBMT on patients' Body Mass Index ( lipid profil e and hepatic biomarkers were also observed by biochemical analysis. METHODOLOGY: Prospective randomized clinical trial among 32 NAFLD patients of both gender aged from 3 5 to 70 years The patients were randomized divided into 2 groups: Placebo Group P.G n=16) and PBMT (PBMT.G n=16), which received irradiation Linealux Laser Therapy ™). CW LED Diode λ 660 nm wavelength) onto sublingual vessels by 3 points in the following dosimetry: Power 5 mW/point; Irradiance 5 mW/cm 2 Total time/application 7 minutes, Spot size 1 cm 2 Fluence 2,1 J/cm 2 were applied. Administered once a week for 16 weeks in total and 1 month follow up post finishing the PBMT application, accounted 20 weeks in total. Both groups underwent by hepatic ultrasonography to pre and post evaluations. All patients to Biochemical analysis (Plasma concentrations) were submitted, such as: Alanine transaminase ( Aspartate transaminase ( Alkaline phosphatase ( Bilirubin (total and fractions), Gamma glutamyl transpeptidase or gamma GT ( Prothrombin Activity Time ( Total Cholesterol and Fractions (HD L LDL) and Tri glycerides to pre and post evaluations. The associations among two categorical variables were analyzed by the C hi S quare test, being that the comparisons of means among two groups by the Student's t test for independent samples and the comparison of means by group PBMT and Placebo) between two moments by ANOVA with repeated measures. A significance level of 5% was used for all statistical tests. RESULTS: In the PBMT group, there was a reduction in hepatic steatosis in 93.8% of the patients observed by ul trasonography. The Placebo group presented a reduction of steatosis in 37.5%, and the chance of decreasing steatosis in the PBMT group was 25 times greater than Placebo. The levels of triglycerides (p < total cholesterol (p < LDL (p < a nd GGT GGT (p(p == 0.005)0.005) inin thethe PBMTPBMT groupgroup decreaseddecreased withwith aa statisticallystatistically significantsignificant response,response, withoutwithout promotingpromoting pathologicalpathological alterationsalterations inin thethe otherother hepatichepatic biomarkers.biomarkers. ThereThere waswas alsoalso aa highlyhighly significantsignificant BMIBMI decreasedecrease inin thethe PBMTPBMT groupgroup (p(p == 0.003)0.003) andand inin thethe PlaceboPlacebo groupgroup thisthis eventevent waswas notnot significantsignificant (p(p == 0.508).0.508). CONCLUSION:CONCLUSION: ThereThere waswas aa significantsignificant reductionreduction inin thethe degreedegree ofof hepatichepatic steatosissteatosis inin thethe groupgroup thatthat underwentunderwent PhotobiomodulationPhotobiomodulation TherapyTherapy byby sublingualsublingual transvasculartransvascular ILIB.ILIB. AA statiscalstatiscal significantsignificant impimprovementrovement waswas alsoalso observedobserved inin allall thethe biochemicalbiochemical andand enzymaticenzymatic parametersparameters analyzedanalyzed inin thethe PBMTPBMT group.group. TheseThese resultsresults indicateindicate thatthat PBMTPBMT,, throughthrough sublingualsublingual application,application, hashas provenproven toto bebe anan effective,effective, safesafe andand systemicsystemic methodmethod forfor patientspatients treatmenttreatment withwith NAFNAFLD,LD, withoutwithout hepatoxicity.hepatoxicity.